1)x*x+60=85
x умножаются,из левой части число 60 переносим в правую часть,причём меняя знак
x²=85-60
x²=25
x₁=5
x₂=-5
2)(x*x-23)*9=117
(x²-23)=117/9
x²-23=13
x²=13+23
x²=36
x₁=6
x₂=-6
3)(x*x*x+38):13=5
(x³+38)=13*5
x³+38=65
x³=65-38
x³=27
x=3
4)(149-x*x*x)*7=168
(149-x³)=168/7
149-x³=24
x³=149-24
x³=125
x=5
X+20=у
у+20=z
x+y+z=90
y+y+20+y-20=3y=90
y=30
x=10
z=50
Ответ:30,10,50
4200/у=42
у=100
вот решение
<span>2x-(4x-((5x-6)+9))) = 2x-(4x-(5x-6+9)) = 2x-(4x-(5x+3)) = 2x-(4x-5x-3) =
= 2x-(-x-3) = 2x+x+3 = 3x+3</span>